A compound and an organic light-emitting device
By deuterated at the active site of the second hole transport compound in the OLED device, the problems of poor chemical stability, thermal stability and photoelectric stability are solved, and higher device life and efficiency are achieved.
Patent Information
- Application Number
- CN202411869518.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The second hole transport compound of existing OLED devices has not been deuterated at the active point and at the high electron cloud density, resulting in poor chemical stability, thermal stability and photoelectric stability, affecting the lifetime of the device.
A compound was designed that is deuterated at the active site of the structure, thereby improving its thermal stability, chemical stability and photoelectric stability, and broadening the exciton composite region by optimizing carrier mobility.
Through the application of deuterated compounds, the lifetime and efficiency of the OLED device are significantly improved, the interface defects between the second hole transport layer and the light emitting layer are reduced, and the overall performance of the device is improved.
Smart Images

Figure CN119306618B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic electroluminescence, and in particular to a compound and an organic light-emitting device. Background Art
[0002] Organic electroluminescence usually refers to an organic light-emitting diode (OLED) that uses electric current to drive an organic semiconductor film to emit light, thereby achieving the purpose of display.
[0003] The composition structure of an organic electroluminescent device includes a cathode, an anode, and an organic layer disposed therebetween. The organic layer structure of OLED devices currently used in the industry is usually a multilayer structure, for example, including a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, a hole blocking layer, an electron transport layer, an electron injection layer and other film layers. For an OLED device including the above-mentioned film layers, when a voltage is applied between the two electrodes, holes are injected from the anode into the organic layer, and electrons are injected from the cathode into the organic layer. When holes and electrons meet, excitons are formed. When the excitons transfer energy to the doping material, light is emitted through the radiation transition of the doping material.
[0004] In existing OLED devices, since the second hole transport compound is not deuterated at the active sites of the material molecules and the sites with high electron cloud density, its chemical stability, thermal stability and photoelectric stability are poor, which in turn affects the life of the device.
[0005] The compounds of the present invention are all deuterated at the active sites of their respective structures, and therefore have good thermal stability, chemical stability and photoelectric stability. At the same time, the materials of the present invention have good carrier mobility, further widen the exciton recombination area, and thus improve the life and efficiency of the device. Summary of the invention
[0006] The purpose of the present invention is to provide a compound and an organic electroluminescent device in view of the above technical problems.
[0007] The purpose of the present invention can be achieved by the following measures:
[0008] A structure as shown in Formula 1:
[0009]
[0010] Ar is selected from the following substituted or unsubstituted groups: phenyl, biphenyl, naphthyl, anthracenyl, dibenzofuranyl, dibenzothiophenyl, fluorenyl, phenanthrenyl, triphenylfuranyl, and the Ar substituent is selected from one or more of deuterium, fluorine, cyano, methyl, deuterated methyl, ethyl, deuterated ethyl, tert-butyl, deuterated tert-butyl, C6-C20 aryl, C6-C20 deuterated aryl, C3-C20 heteroaryl, and C3-C20 deuterated heteroaryl;
[0011] L is a direct bond, a substituted or unsubstituted group: a C6-C12 aryl group, a C3-C20 heteroaryl group, and the L substituent is selected from one or more of deuterium, fluorine, cyano, methyl, deuterated methyl, ethyl, deuterated ethyl, tert-butyl, deuterated tert-butyl, phenyl, deuterated phenyl, pyridyl, and pyrimidyl;
[0012] R1 and R2 are independently selected from one or more of hydrogen, deuterium, cyano, deuterated or undeuterated C1-C6 alkyl, deuterated or undeuterated C3-C8 cycloalkyl;
[0013] A1-A7 are hydrogen or deuterium, wherein at least one of A5-A7 is deuterium;
[0014] The present invention does not include the following compounds:
[0015]
[0016] Preferably, Ar is independently selected from the following substituted or unsubstituted groups: phenyl, biphenyl, dibenzofuranyl, dibenzothiophenyl, fluorenyl, and the Ar substituent is selected from one or more of deuterium, fluorine, cyano, methyl, deuterated methyl, ethyl, deuterated ethyl, tert-butyl, deuterated tert-butyl, C6-C12 aryl, C6-C12 deuterated aryl;
[0017] L is a direct bond, a substituted or unsubstituted C6-C12 aryl group, and the L substituent is selected from one or more of deuterium, fluorine, cyano, methyl, deuterated methyl, ethyl, deuterated ethyl, tert-butyl, deuterated tert-butyl, phenyl, and deuterated phenyl;
[0018] R1 and R2 are independently selected from one or more of hydrogen, deuterium, cyano, methyl, deuterated methyl, ethyl, deuterated ethyl, tert-butyl, and deuterated tert-butyl;
[0019] A1-A7 are hydrogen or deuterium, wherein at least one of A5-A7 is deuterium.
[0020] Preferably, Ar is selected from the following substituted or unsubstituted groups: phenyl, biphenyl, fluorenyl, and the Ar substituent is selected from one or more of deuterium, methyl, deuterated methyl, ethyl, deuterated ethyl, tert-butyl, deuterated tert-butyl, phenyl, and deuterated phenyl;
[0021] L is a direct bond, a substituted or unsubstituted C6-C12 aryl group, and the L substituent is selected from one or more of deuterium, fluorine, cyano, methyl, and deuterated methyl;
[0022] R1 and R2 are independently selected from one or more of hydrogen, deuterium, cyano, methyl, deuterated methyl, tert-butyl, and deuterated tert-butyl;
[0023] A1-A7 are hydrogen or deuterium, wherein at least one of A5-A7 is deuterium.
[0024] Further preferably, Ar is selected from the following substituted or unsubstituted groups: phenyl, biphenyl, fluorenyl, and the Ar substituent is selected from one or more of deuterium, methyl, deuterated methyl, tert-butyl, deuterated tert-butyl;
[0025] L is a direct bond, a substituted or unsubstituted phenyl group, or a substituted or unsubstituted biphenyl group, wherein the L substituent is selected from one or more of deuterium, fluorine, cyano, methyl, and deuterated methyl;
[0026] R1 and R2 are independently selected from one or more of hydrogen, deuterium, methyl, deuterated methyl, tert-butyl, and deuterated tert-butyl;
[0027] A1-A7 are hydrogen or deuterium, wherein at least one of A5-A7 is deuterium.
[0028] More preferably, Ar is selected from the following substituted or unsubstituted groups: phenyl, biphenyl, fluorenyl, and the Ar substituent is selected from one or more of deuterium, methyl, and deuterated methyl;
[0029] L is a direct bond, a substituted or unsubstituted phenyl group, or a substituted or unsubstituted biphenyl group, wherein the L substituent is selected from one or more of deuterium, methyl, and deuterated methyl;
[0030] R1 and R2 are independently selected from one or more of hydrogen, deuterium, tert-butyl, and deuterated tert-butyl;
[0031] A1-A7 are hydrogen or deuterium, wherein at least one of A5-A7 is deuterium.
[0032] In a preferred embodiment, the compound of the present invention can be any one of the following structural formulas:
[0033] .
[0034] A composition comprising compounds, wherein the deuteration rate of A5 of the compounds contained in the composition is 0%-50%, the deuteration rate of A6 is 10%-100%, and the deuteration rate of A7 is 40%-100%.
[0035] Furthermore, the deuteration rate of A5 of the compound contained in the composition is 0%-30%, the deuteration rate of A6 is 20%-100%, and the deuteration rate of A7 is 60%-100%.
[0036] Furthermore, the deuteration rate of A5 of the compound contained in the composition is 0%-10%, the deuteration rate of A6 is 30%-80%, and the deuteration rate of A7 is 60%-98%.
[0037] Furthermore, the deuteration rate of A5 of the compound contained in the composition is 0%-5%, the deuteration rate of A6 is 40%-60%, and the deuteration rate of A7 is 80%-95%.
[0038] An organic electroluminescent device comprises a first electrode, a second electrode and an organic layer formed between the first electrode and the second electrode, wherein the organic layer contains the organic electroluminescent compound mentioned above.
[0039] Furthermore, the organic layer comprises a hole injection layer, a hole transport layer, a second hole transport layer, a light-emitting layer, a hole blocking layer, an electron transport layer, and an electron injection layer; at least one of the hole injection layer, the hole transport layer, the second hole transport layer, the light-emitting layer, the hole blocking layer, the electron transport layer, and the electron injection layer contains the above-mentioned organic electroluminescent compound.
[0040] Furthermore, the second hole transport layer contains the above-mentioned organic electroluminescent compound.
[0041] The compound of the invention is applied to the organic electroluminescent device, and the organic electroluminescent device can be used in the field of manufacturing electronic display equipment or OLED lighting equipment.
[0042] Beneficial effects of the present invention:
[0043] The present invention relates to a novel organic electroluminescent compound, which realizes the synergistic improvement of multiple excellent properties through the careful design of the molecular structure.
[0044] 1. Since they are all deuterated at the active sites of their respective structures, they all have good thermal stability, chemical stability and photoelectric stability.
[0045] 2. At the same time, the compounds of the present invention have good carrier mobility, further broadening the exciton recombination area, thereby improving the life and efficiency of the device.
[0046] 3. Since the current GH material is a deuterated compound, the introduction of deuterium into the second hole transport material can effectively reduce the interface defects between the second hole transport layer and the light-emitting layer, thereby effectively improving the efficiency and life of the device.
[0047] 4. The compound intermediate is subjected to a deuteration reaction. The mixture with different deuteration rates after the reaction can be directly subjected to the next reaction without further separation, which is beneficial to saving production costs. The device prepared by the synthetic composition also has higher efficiency and lifespan. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 A schematic diagram of the structure of an organic electroluminescent device provided by the present invention;
[0049] The numbers in the figure represent: 1-anode, 2-hole injection layer, 3-hole transport layer, 4-second hole transport layer, 5-light-emitting layer, 6-hole blocking layer, 7-electron transport layer, 8-electron injection layer, 9-cathode.
[0050] Figure 2 It is the HPLC chart of compound 2 of the present invention.
[0051] Figure 3 is the DSC spectrum of compound 2 prepared in Example 1 of the present invention, Figure 3 It can be seen that the glass transition temperature Tg value of compound 2 is 162.51°C.
[0052] Figure 4 is the TGA spectrum of compound 2 of the present invention, Figure 4 It can be seen that the thermal weight loss temperature Td value of compound 2 is 400.54°C. DETAILED DESCRIPTION
[0053] The following further illustrates and describes embodiments of various aspects. It should be understood that the description herein is not intended to limit the claims to the specific aspects described. On the contrary, it is intended to cover substitutions, modifications and equivalents that may be included in the spirit and scope of the present disclosure defined by the appended claims.
[0054] As used herein, in "deuterated" or "undeuterated", the term "deuterated" means that at least one hydrogen in the group is re-coordinated with deuterium. The term "undeuterated" means that all hydrogens in the group are not re-coordinated with deuterium.
[0055] The "aromatic group", "aryl" or "aromatic group" herein refers to a group containing one or more aromatic rings, and the aromatic rings here include but are not limited to benzene, naphthalene, phenanthrene, fluorene, acenaphthene, pyridine, pyrimidine, pyrrole, furan, thiophene, etc. The C5-C40 in the C5-C40 aromatic group means that the group contains 5-40 carbon atoms. Aromatic groups can be divided into monocyclic aromatic groups and polycyclic aromatic groups. Specific aromatic groups in the present invention include but are not limited to phenyl, biphenyl, terphenyl, anthracenyl, naphthyl, phenanthryl, fluorenyl, dibenzofuranyl, dibenzothiophenyl, 9,9-spirobifluorenyl, 9,9-dimethylfluorenyl or 9,9-diphenylfluorenyl, etc. Aromatic groups can be substituted and unsubstituted.
[0056] "Cycloalkyl" herein refers to a monocyclic or fused ring ("fused" ring means that each ring in the system shares a pair of adjacent carbon atoms with other rings in the system) group that is all carbon, wherein one or more rings are saturated alicyclic rings, which generally have 3-20 carbon atoms, preferably 3-12 carbon atoms, and more preferably 3-10 carbon atoms. Cycloalkyl can be divided into monocyclic alkyls having only one ring and fused cyclic alkyls having multiple rings. Examples of monocyclic alkyls include, but are not limited to, cyclopropane, cyclobutane, cyclopentane, cyclohexane, cycloheptane. Cycloalkyl can be substituted and unsubstituted.
[0057] "Cycloalkenyl" herein refers to a monocyclic or fused ring ("fused" ring means that each ring in the system shares a pair of adjacent carbon atoms with other rings in the system) group that is all carbon, wherein one or more rings do not have a completely connected π electron system and contain at least one alkenyl group, which generally has 3-20 carbon atoms, preferably 3-12 carbon atoms, more preferably 3-10 carbon atoms, and the examples of cycloalkenyl groups include but are not limited to cyclopentene, cyclohexene, cyclohexadiene, cycloheptatriene. Cycloalkenyl groups may be substituted and unsubstituted.
[0058] The "deuterated aryl group" herein refers to a group in which one or more hydrogen atoms in an aromatic group are substituted with deuterium.
[0059] The "deuterated phenyl group" herein refers to a group in which one or more hydrogen atoms in a phenyl group are replaced by deuterium.
[0060] The “heteroaryl group” herein refers to a heteroaryl group obtained by replacing one or more C atoms in the structure of the “aryl group” with one or more heteroatoms (such as N, O or S).
[0061] The "deuteration rate" in this article refers to the probability that the group at the site is replaced by deuterium. For example, "the deuteration rate of compound A5 is 0%-50%" means that the minimum probability of the site of compound A5 being replaced by deuterium is 0% and the maximum probability is 50%.
[0062] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0063] Example 1
[0064]
[0065] Compound 2 was prepared as follows:
[0066] Step 1:
[0067]
[0068] 1-a (50 g, 0.187 mol, 1 eq) and deuterated benzene (157.4 g, 1.87 mol, 10 eq) were added to a 1 L single-necked flask, and trifluoromethanesulfonic acid (196 g, 1.309 mol, 7 eq) was added dropwise. After the addition, the temperature was raised to 50 °C for reaction for 5-6 h to stop the reaction, and the temperature was lowered. The reaction solution was slowly poured into a 1 L ice-water bath, and ethyl acetate (300 ml*3) was added for extraction. The organic phases were combined, washed with water and saturated brine, dried over anhydrous sodium sulfate, and concentrated to dryness under reduced pressure. 80 g of 100-200 mesh silica gel sand was added, and 500 g of 100-200 mesh silica gel was loaded on the column. Column chromatography was performed, and pure PE was rinsed. The product points were collected and concentrated to dryness under reduced pressure to obtain 41 g of off-white solid with a yield of 79.6%.
[0069] Step 2:
[0070]
[0071] Add 1-b (39 g, 0.142 mol, 1 eq) and ultra-dry THF (200 ml) to a 1L three-necked flask, cool to -78°C, add 2.5 M n-butyl lithium (59.5 ml, 0.149 mol, 1.05 eq) dropwise, keep stirring at -78°C for 1 h, add 1-c (39.3 g, 0.134 mol, 0.95 eq) in THF (200 ml) dropwise, warm to room temperature and stir to react overnight. Stop the reaction, add ammonium chloride aqueous solution, stir and separate, extract the aqueous phase with DCM, combine the organic phases, and concentrate to dryness under reduced pressure to obtain the product 1-d, which is used directly in the next step without purification.
[0072] 1-d (theoretical 69.4 g, 0.142 mol, 1 eq) and DCM (700 mL) were added to a 2L single-necked flask, cooled to below 0°C, and methanesulfonic acid (81.9 g, 0.852 mol, 6 eq) was added. After the addition was complete, the reaction was stirred for 1 h. HPLC monitored 1-d ≤ 0.5%. The reaction was stopped, 200 ml of ethanol was added, and most of the DCM was removed by low-temperature and reduced pressure concentration. A large amount of solid was precipitated, and the filter cake was washed with ethanol 2 to 3 times. The filter cake was dried at 85°C to obtain 43 g of off-white solid 1-c, with a two-step yield of 64.2%.
[0073] Step 3:
[0074]
[0075] 1-e (40 g, 84.75 mmol, 1 eq), 1-f (34 g, 84.75 mmol, 1 eq), sodium tert-butoxide (9.8 g, 0.102 mol, 1.2 eq), XPhos (1.62 g, 3.39 mmol, 0.04 eq) and toluene (300 ml) were added to a 1 L three-necked flask. Palladium acetate (0.38 g, 1.695 mmol, 0.02 eq) was added under N2 protection. After the addition was completed, the temperature was raised to 100 °C and the reaction was stirred. HPLC monitored 1-e ≤ 0.5%. Stop the reaction, filter through silica gel while hot, concentrate the filtrate to dryness under reduced pressure, add 100 ml of toluene and 400 ml of ethanol, stir and beat at 65°C for 2 h, cool and stir to crystallize overnight, filter, recrystallize the filter cake with toluene / ethanol three times, filter, recrystallize the filter cake with toluene once, filter, and dry the filter cake at 85°C to obtain 42 g of off-white solid as compound 2 with HPLC purity of 99.99% and a yield of 59.2%.
[0076] Compounds 1, 4, 8, 10, 20, 26, 32, 37, 48, 50, 56, 64, 66, 74, 87, 90, 98, 100, 102, 104, 110, 112, 116, 120, 122, 126, 130, 132, 135, 138, 146, 148, 150, 151, 154 were obtained in a similar manner. See Tables 1-1, 1-2, 1-3, 1-4, 1-5, 1-6, 1-7, 1-8, 1-9, 1-10, 1-11, 1-12 for details:
[0077] Table 1-1
[0078]
[0079] Table 1-2
[0080]
[0081] Table 1-3
[0082]
[0083] Table 1-4
[0084]
[0085] Table 1-5
[0086]
[0087] Table 1-6
[0088]
[0089] Table 1-7
[0090]
[0091] Table 1-8
[0092]
[0093] Table 1-9
[0094]
[0095] Table 1-10
[0096]
[0097] Table 1-11
[0098]
[0099] Table 1-12
[0100]
[0101] Embodiment 37
[0102]
[0103] Compound 161 was prepared as follows:
[0104] Step 1:
[0105]
[0106] Add 2-a (100g, 0.315mol, 1eq), 2-b (59.5g, 0.331mol, 1.05eq), potassium carbonate (87g, 0.63mol, 2eq), Pd (PPd3) 4 (7.28g, 6.3mmol, 0.02eq) and toluene / ethanol / water (1000 ml + 500 ml + 300 ml) to a 2L three-necked flask, and heat and reflux to react under N2 protection, and monitor HPLC until 2-a ≤ 0.5%. Stop the reaction, add 200ml of water, stir and separate the liquids, separate the organic phase, extract the aqueous phase with DCM, combine the organic phases, filter through silica gel, and concentrate to dryness under reduced pressure to obtain 2-c, which is directly used in the next step without purification.
[0107] Add 2-c (theoretical 102.6g, 0.315mol, 1eq), 2mol / L sodium hydroxide aqueous solution (315ml) and ethanol (500ml) to a 2L single-necked bottle, heat to 65℃ and stir to react for 2h, monitor by TLC until 2-C basically disappears. Stop the reaction, cool to room temperature, adjust pH to 2~3 with 4mol / L hydrochloric acid solution, precipitate a large amount of solid, filter, rinse the filter cake with water, dry the filter cake at 85℃, and obtain 84g of off-white solid, with a two-step yield of 85.6%.
[0108] Step 2:
[0109]
[0110] 2-d (80 g, 0.257 mol, 1 eq) and thionyl chloride (400 ml) were added to a 1 L three-necked flask, and the mixture was stirred under reflux and heated for 72 h. The reaction was stopped, and the mixture was concentrated to dryness under reduced pressure. 100 g of 100-200 mesh silica gel sand was added, and 500 g of 100-200 mesh silica gel was loaded into a column for column chromatography. The mixture was rinsed with pure petroleum ether, and the product points were collected. The mixture was concentrated to dryness under reduced pressure to obtain 56 g of off-white solid 2-e with a yield of 74.2%.
[0111] 2-e (56 g, 0.191 mol, 1 eq) and ultra-dry THF (300 ml) were added to a 1L three-necked flask, cooled to -78°C, 2.5 M n-butyl lithium (80 ml, 0.2 mol, 1.05 eq) was added dropwise, and after the addition was completed, the mixture was stirred and reacted at -78°C for 1 h, and heavy water (38.2 g, 1.91 mol, 10 eq) was added dropwise. After the addition was completed, the mixture was heated to room temperature and stirred and reacted overnight. The reaction was stopped, and an aqueous ammonium chloride solution was added, stirred and separated, the aqueous phase was extracted with DCM, the organic phases were combined, concentrated to dryness under reduced pressure, 200 ml of petroleum ether was added, heated to reflux and slurried for 2 h, cooled to room temperature, filtered, and the filter cake was dried with air at 85°C to obtain 37.2 g of pink solid 2-f with a yield of 90.3%.
[0112] Step 3:
[0113]
[0114] Add 2-g (62.7g, 0.182mol, 1eq) and ultra-dry THF (350ml) to a 1L three-necked flask, cool to -78°C, add 2.5M n-butyl lithium (80ml, 0.191mol, 1.05eq) dropwise, keep stirring at -78°C for 1h, add 2-f (37.2g, 0.173mol, 0.95eq) in THF (150ml) dropwise, after the addition is complete, warm to room temperature and stir to react overnight. Stop the reaction, add ammonium chloride aqueous solution, stir and separate, extract the aqueous phase with DCM, combine the organic phases, and concentrate to dryness under reduced pressure to obtain 2-h, which is directly used in the next step without purification.
[0115] 2-h (theoretical 83.2 g, 0.173 mol, 1 eq) and DCM (500 mL) were added to a 2L single-necked flask, cooled to below 0°C, and methanesulfonic acid (66.5 g, 0.692 mol, 4 eq) was added. After the addition was complete, the reaction was stirred for 1 h. HPLC monitored 2-h ≤ 0.5%. The reaction was stopped, 200 ml of ethanol was added, and most of the DCM was removed by low-temperature and reduced pressure concentration. A large amount of solid was precipitated, and the filter cake was washed with ethanol 2 to 3 times. The filter cake was dried at 85°C to obtain 59 g of off-white solid 2-i, with a two-step yield of 73.5%.
[0116] Step 4:
[0117] Further synthesis was carried out according to step 3 of the synthesis method of Example 1 to obtain 43 g of compound 161 with a yield of 61.2%.
[0118] Compounds 163, 164, 165, 168, 169, 172, 175, 180, 183, 187, 192, 200, 208, 210, 215, 219, 225, 227, 229, 230, 231, 232, 235, 236, 237, 239, 240, 243 were obtained in a similar manner. See Table 2-1, Table 2-2, Table 2-3, Table 2-4, Table 2-5, Table 2-6, Table 2-7, Table 2-8, Table 2-9 for details:
[0119] Table 2-1
[0120]
[0121] Table 2-2
[0122]
[0123] Table 2-3
[0124]
[0125] Table 2-4
[0126]
[0127] Table 2-5
[0128]
[0129] Table 2-6
[0130]
[0131] Table 2-7
[0132]
[0133] Table 2-8
[0134]
[0135] Table 2-9
[0136]
[0137] Embodiment 66
[0138]
[0139] Compound 245 was prepared as follows:
[0140]
[0141] CP8565-SM1 (50g, 0.187mol, 1eq), silver carbonate (10.3g, 37.4mmol, 0.2eq), diphenylcyclohexylphosphine (25.1g, 93.5mmol, 0.5eq), heavy water (74.8g, 3.74mol, 20eq) and toluene (18.7ml) were added to a 1L single-necked bottle, and the temperature was raised to 120°C and stirred for 24h. The reaction was stopped, filtered through silica gel, the filtrate was added with DCM and stirred for separation, the aqueous phase was extracted with DCM, the organic phase was combined and concentrated to dryness under reduced pressure, purified by column chromatography (pure PE rinse), the product points were collected, concentrated to dryness under reduced pressure, and then deuterated (re-dosed according to the above-mentioned feed amount and post-processed), and finally 39.5g of off-white solid was obtained with a yield of 76.7%.
[0142] The remaining steps were further synthesized according to steps 2 and 3 in the synthesis method of Example 1 to obtain 41 g of compound 161 with a yield of 57.4%.
[0143] Compounds 249, 251, 259, 263, 265, 267, and 268 were obtained in a similar manner. See Table 3-1 and Table 3-2 for details:
[0144] Table 3-1
[0145]
[0146] Table 3-2
[0147]
[0148] The synthetic identification results of the compounds prepared in Tables 1-1, 1-2, 1-3, 1-4, 1-5, 1-6, 1-7, 1-8, 1-9, 1-10, 1-11, 1-12, 2-1, 2-2, 2-3, 2-4, 2-5, 2-6, 2-7, 2-8, 2-9, 3-1, and 3-2 above are shown in Table 4 below:
[0149] Table 4
[0150] Compound FD-Quality Compound FD-Quality 1 m / z=829.91(C63H54D3N=830.47) 163 m / z=829.32(C63H55D2N=829.46) 2 m / z=833.95(C63H50D7N=834.49) 164 m / z=833.34(C63H51D6N=833.49) 4 m / z=793.95(C60H46D7N=794.46) 165 m / z=827.89(C63H56DN=828.46) 8 m / z=793.97(C60H46D7N=794.46) 168 m / z=833.31(C63H51D6N=833.49) 10 m / z=777.92(C59H42D7N=778.43) 169 m / z=827.95(C63H56DN=828.46) 20 m / z=681.88(C52H30D7N=682.34) 172 m / z=833.36(C63H51D6N=833.49) 26 m / z=833.95(C63H50D7N=834.49) 175 m / z=717.11(C55H39D2N=717.34) 32 m / z=793.94(C60H46D7N=794.46) 180 m / z=721.24(C55H35D6N=721.36) 37 m / z=777.96(C59H42D7N=778.43) 183 m / z=717.27(C55H39D2N=717.34) 48 m / z=681.87(C52H30D7N=682.34) 187 m / z=789.34(C60H51D2N=789.43) 50 m / z=833.94(C63H50D7N=834.49) 192 m / z=793.31(C60H47D6N=793.46) 56 m / z=793.97(C60H46D7N=794.46) 200 m / z=681.22(C52H31D6N=681.33) 64 m / z=737.93(C56H38D7N=738.40) 208 m / z=681.23(C52H31D6N=681.33) 66 m / z=721.88 (C55H34D7N=722.37) 210 m / z=791.92(C60H48D5N=792.45) 74 m / z=833.97(C63H50D7N=834.49) 215 m / z=789.39(C60H51D2N=789.43) 87 m / z=721.95(C55H34D7N=722.37) 219 m / z=677.28(C52H35D2N=677.31) 90 m / z=721.94 (C55H34D7N=722.37) 225 m / z=675.94(C52H36DN=676.30) 98 m / z=833.92(C63H50D7N=834.49) 227 m / z=677.27(C52H35D2N=677.31) 100 m / z=833.94(C63H50D7N=834.49) 229 m / z=803.41(C61H53D2N=803.45) 102 m / z=807.96(C61H48D7N=808.48) 230 m / z=803.39(C61H53D2N=803.45) 104 m / z=807.95(C61H48D7N=808.48) 231 m / z=695.27(C53H33D6N=695.35) 110 m / z=811.49(C61H45D10N=811.50) 232 m / z=695.23(C53H33D6N=695.35) 112 m / z=811.48(C61H45D10N=811.50) 235 m / z=803.38(C61H53D2N=803.45) 116 m / z=721.87(C55H34D7N=722.37) 236 m / z=691.19(C53H37D2N=691.32) 120 m / z=807.98(C61H48D7N=808.48) 237 m / z=691.24(C53H37D2N=691.32) 122 m / z=833.96(C63H50D7N=834.49) 239 m / z=695.27(C53H33D6N=695.35) 126 m / z=811.41(C61H45D10N=811.50) 240 m / z=807.38(C61H49D6N=807.47) 130 m / z=807.97(C61H48D7N=808.48) 243 m / z=789.40(C60H51D2N=789.43) 132 m / z=807.96(C61H48D7N=808.48) 245 m / z=831.97(C63H52D5N=832.48) 135 m / z=695.89(C53H32D7N=696.35) 249 m / z=805.95(C61H50D5N=806.46) 138 m / z=811.42(C61H45D10N=811.50) 251 m / z=805.94(C61H50D5N=806.46) 146 m / z=807.95(C61H48D7N=808.48) 259 m / z=805.94(C61H50D5N=806.46) 148 m / z=807.93(C61H48D7N=808.48) 263 m / z=809.31(C61H47D8N=809.48) 150 m / z=807.94(C61H48D7N=808.48) 265 m / z=791.89(C60H48D5N=792.45) 151 m / z=695.97(C53H32D7N=696.35) 267 m / z=829.95(C63H54D3N=830.47) 154 m / z=811.45(C61H45D10N=811.50) 268 m / z=829.95(C63H54D3N=830.47) 161 m / z=827.96(C63H56DN=828.46)
[0151] The above materials were subjected to basic performance tests, including thermal weight loss temperature Td and glass transition temperature Tg. The test results are shown in Table 5 below.
[0152] Note: Thermal weight loss temperature Td is the temperature at which the weight loss ratio is 5% in a nitrogen atmosphere, and is measured on a TGA N-1000 thermogravimetric analyzer with a nitrogen flow rate of 10 mL / min. Tg (glass transition temperature) is measured by differential scanning calorimetry (DSC, Shinco DSC N-650) with a heating rate of 10°C / min.
[0153] Table 5
[0154] Test material (compound) Tg / ℃ Td / ℃ Test material (compound) Tg / ℃ Td / ℃ 1 171.22 402.73 163 172.37 408.68 2 162.51 400.54 164 163.24 392.10 4 156.34 389.18 165 158.21 392.15 8 179.55 397.24 168 165.36 388.04 10 164.27 391.10 169 162.54 397.32 20 170.54 397.21 172 148.35 396.24 26 177.69 391.20 175 154.26 381.35 32 174.25 387.35 180 175.85 387.94 37 166.42 388.85 183 153.10 408.32 48 164.75 405.14 187 163.82 400.35 50 156.10 375.74 192 165.22 395.79 56 153.54 381.85 200 156.54 371.52 64 164.69 397.25 208 159.47 380.63 66 176.24 394.34 210 172.23 395.40 74 154.68 387.80 215 176.53 412.93 87 173.78 395.17 219 166.53 401.64 90 165.12 376.24 225 158.74 381.41 98 167.35 386.71 227 155.42 399.23 100 159.08 396.03 229 153.97 384.87 102 152.29 378.49 230 171.37 384.87 104 181.47 396.34 231 168.60 404.47 110 171.28 394.52 232 171.48 389.74 112 160.57 375.46 235 159.05 397.16 116 174.41 403.87 236 163.81 380.58 120 154.25 394.50 237 158.47 390.43 122 158.57 375.91 239 169.35 402.80 126 165.70 401.29 240 160.02 386.14 130 179.81 397.64 243 174.20 398.38 132 156.84 387.92 245 159.43 388.69 135 154.46 386.27 249 157.62 394.58 138 159.54 387.68 251 169.35 397.01 146 174.21 376.33 259 161.49 375.94 148 161.65 386.21 263 165.39 387.65 150 176.12 397.35 265 176.32 396.54 151 154.57 397.25 267 166.89 398.21 154 173.57 388.36 268 161.28 396.55 161 156.71 402.94
[0155] According to the above data, the compounds synthesized in the present invention have excellent thermal stability, which means that the compounds conforming to the general structural formula of the present invention have excellent thermal stability and can meet the requirements for the use of organic electroluminescent materials.
[0156] Device performance test:
[0157] Application Example 1:
[0158] ITO was used as the reflective layer anode substrate material, and its surface was treated with water, acetone, and N2 plasma in sequence;
[0159] On top of the ITO anode substrate, 10 nm of HT-1 doped with 5% NDP-9 was deposited to form a hole injection layer (HIL);
[0160] A hole transport layer (HTL) was formed by evaporating 100 nm of HT-1 on the hole injection layer (HIL);
[0161] Vacuum evaporating the compound 2 of the present invention on the hole transport layer (HTL) to form a second hole transport layer (GPL) with a thickness of 10 nm;
[0162] GH-2 and GH-1 were co-evaporated at a ratio of 5:5 (mass ratio) as the main luminescent materials, and GD-1 was evaporated as the doping material (the amount of GD-1 was 8% of the total weight of GH-1 and GH-2) on the second hole transport layer (GPL) to form a luminescent layer with a thickness of 20 nm;
[0163] HB-1 was evaporated onto the light-emitting layer to obtain a hole blocking layer (HBL) with a thickness of 20 nm;
[0164] ET-1 and LiQ were co-evaporated onto the hole blocking layer (HBL) at a ratio of 5:5 to obtain an electron transport layer (ETL) with a thickness of 30 nm;
[0165] Magnesium (Mg) and silver (Ag) were mixed in a ratio of 9:1 and evaporated onto the electron transport layer (ETL) to form an electron injection layer (EIL) with a thickness of 50 nm.
[0166] After that, silver (Ag) is evaporated on the electron injection layer to form a cathode with a thickness of 100nm, and DNTPD with a thickness of 50nm is deposited on the cathode sealing layer. In addition, the cathode surface is sealed with a UV curable adhesive and a sealing film (seal cap) containing a dehumidifier to protect the organic electroluminescent device from being affected by oxygen or moisture in the atmosphere. Thus, an organic electroluminescent device is prepared.
[0167]
[0168] Application Example 2-73
[0169] Respectively with compounds 1, 4, 8, 10, 20, 26, 32, 37, 48, 50, 56, 64, 66, 74, 87, 90, 98, 100, 102, 104, 110, 112, 116, 120, 122, 126, 130, 132, 135, 138, 146, 148, 150, 151, 154, 161, 163, 164, 165, 168, 169, 172 in Examples 2-36 of the present invention , 175, 180, 183, 187, 192, 200, 208, 210, 215, 219, 225, 227, 229, 230, 231, 232, 235, 236, 237, 239, 240, 243, 245, 249, 251, 259, 263, 265, 267, 268 as the second hole transport material, and the other parts are consistent with those in Application Example 1, and the organic electroluminescent device of Application Example 2-73 is manufactured based on this.
[0170] Comparative Examples 1-6:
[0171] The difference from Application Example 1 is that compound D1 in patent CN104114672 A, compound D2 in patent CN112010760A and compounds D3, D4, D5 and D6 in patent CN116323559A are used as the second hole transport material, and the rest is the same as Application Example 1.
[0172] The characteristics of the organic electroluminescent device manufactured in the above application example and the organic electroluminescent device manufactured in the control example were measured under the condition of a current density of 10 mA / cm2. The results are shown in Table 6 below.
[0173] Table 6
[0174] Experimental Group Second hole transport layer <![CDATA[Current density (mA / cm 2 ).]]> Voltage (V) Luminous efficiency Emitting color Comparative Example 1 D1 10 3.70 157.6 Green Light Comparative Example 2 D2 10 3.76 161.4 Green Light Comparative Example 3 D3 10 3.65 168.5 Green Light Comparative Example 4 D4 10 3.69 170.1 Green Light Comparative Example 5 D5 10 3.71 172.5 Green Light Comparative Example 6 D6 10 3.67 167.2 Green Light Application Example 1 2 10 3.25 213.1 Green Light Application Example 2 1 10 3.32 207.5 Green Light Application Example 3 4 10 3.44 190.2 Green Light Application Example 4 8 10 3.43 195.7 Green Light Application Example 5 10 10 3.31 199.4 Green Light Application Example 6 20 10 3.40 181.5 Green Light Application Example 7 26 10 3.35 193.5 Green Light Application Example 8 32 10 3.41 186.2 Green Light Application Example 9 37 10 3.32 199.8 Green Light Application Example 10 48 10 3.44 190.6 Green Light Application Example 11 50 10 3.28 195.9 Green Light Application Example 12 56 10 3.48 191.2 Green Light Application Example 13 64 10 3.30 196.4 Green Light Application Example 14 66 10 3.28 207.3 Green Light Application Example 15 74 10 3.31 194.2 Green Light Application Example 16 87 10 3.28 198.5 Green Light Application Example 17 90 10 3.33 206.0 Green Light Application Example 18 98 10 3.28 195.7 Green Light Application Example 19 100 10 3.26 199.5 Green Light Application Example 20 102 10 3.43 184.1 Green Light Application Example 21 104 10 3.42 191.3 Green Light Application Example 22 110 10 3.39 182.4 Green Light Application Example 23 112 10 3.44 188.9 Green Light Application Example 24 116 10 3.23 193.6 Green Light Application Example 25 120 10 3.40 189.3 Green Light Application Example 26 122 10 3.26 197.4 Green Light Application Example 27 126 10 3.43 191.5 Green Light Application Example 28 130 10 3.44 194.6 Green Light Application Example 29 132 10 3.46 189.3 Green Light Application Example 30 135 10 3.42 184.5 Green Light Application Example 31 138 10 3.41 183.2 Green Light Application Example 32 146 10 3.38 180.9 Green Light Application Example 33 148 10 3.37 181.4 Green Light Application Example 34 150 10 3.40 188.3 Green Light Application Example 35 151 10 3.44 192.1 Green Light Application Example 36 154 10 3.39 187.9 Green Light Application Example 37 161 10 3.26 198.3 Green Light Application Example 38 163 10 3.32 191.5 Green Light Application Example 39 164 10 3.27 187.2 Green Light Application Example 40 165 10 3.30 201.9 Green Light Application Example 41 168 10 3.22 194.8 Green Light Application Example 42 169 10 3.24 189.0 Green Light Application Example 43 172 10 3.28 196.4 Green Light Application Example 44 175 10 3.25 186.1 Green Light Application Example 45 180 10 3.29 203.4 Green Light Application Example 46 183 10 3.38 192.7 Green Light Application Example 47 187 10 3.43 191.0 Green Light Application Example 48 192 10 3.45 190.9 Green Light Application Example 49 200 10 3.48 186.5 Green Light Application Example 50 208 10 3.49 193.2 Green Light Application Example 51 210 10 3.47 187.9 Green Light Application Example 52 215 10 3.41 194.4 Green Light Application Example 53 219 10 3.39 187.9 Green Light Application Example 54 225 10 3.40 202.6 Green Light Application Example 55 227 10 3.36 194.4 Green Light Application Example 56 229 10 3.37 186.7 Green Light Application Example 57 230 10 3.21 201.2 Green Light Application Example 58 231 10 3.35 189.7 Green Light Application Example 59 232 10 3.44 196.1 Green Light Application Example 60 235 10 3.45 188.4 Green Light Application Example 61 236 10 3.33 192.1 Green Light Application Example 62 237 10 3.29 190.8 Green Light Application Example 63 239 10 3.31 187.2 Green Light Application Example 64 240 10 3.39 195.2 Green Light Application Example 65 243 10 3.37 186.3 Green Light Application Example 66 245 10 3.24 203.5 Green Light Application Example 67 249 10 3.30 176.7 Green Light Application Example 68 251 10 3.34 181.2 Green Light Application Example 69 259 10 3.35 185.6 Green Light Application Example 70 263 10 3.27 198.2 Green Light Application Example 71 265 10 3.32 186.7 Green Light Application Example 72 267 10 3.24 194.0 Green Light Application Example 73 268 10 3.27 196.8 Green Light
[0175] As can be seen from the above table, when the material of the present invention is applied to an organic electroluminescent device, at the same current density, the luminous efficiency is greatly improved, the starting voltage of the device is reduced, and the power consumption of the device is relatively reduced.
[0176] The organic electroluminescent devices prepared in the control examples 1-6, application examples 1-15, 37-44, 66, and 67 were respectively subjected to luminescence life tests to obtain luminescence life T97% data (the time when the luminescence brightness decreases to 97% of the initial brightness). The test equipment was a TEO luminescent device life test system. The results are shown in Table 7:
[0177] Table 7
[0178] Experimental Group Hole Transport Materials (HTL) <![CDATA[Current density (mA / cm 2 )]]> T97% Comparative Example 1 D1 10 95% Comparative Example 2 D2 10 96% Comparative Example 3 D3 10 100% Comparative Example 4 D4 10 105% Comparative Example 5 D5 10 108% Comparative Example 6 D6 10 102% Application Example 1 2 10 146% Application Example 2 1 10 138% Application Example 3 4 10 127% Application Example 4 8 10 124% Application Example 5 10 10 139% Application Example 6 20 10 126% Application Example 7 26 10 136% Application Example 8 32 10 123% Application Example 9 37 10 137% Application Example 10 48 10 126% Application Example 11 50 10 138% Application Example 12 56 10 127% Application Example 13 64 10 143% Application Example 14 66 10 141% Application Example 15 74 10 139% Application Example 37 161 10 134% Application Example 38 163 10 137% Application Example 39 164 10 125% Application Example 40 165 10 123% Application Example 41 168 10 131% Application Example 42 169 10 122% Application Example 43 172 10 136% Application Example 44 175 10 135% Application Example 66 245 10 142% Application Example 67 249 10 134%
[0179] It can be seen from the above table that when the material of the present invention is applied to an organic electroluminescent device, the service life is greatly improved at the same current density, and the material has broad application prospects.
[0180] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A compound, characterized in that Selected from the structure shown in Formula 1: ; In formula 1, Ar is selected from the following substituted or unsubstituted groups: phenyl, biphenyl, fluorenyl, and the Ar substituent is selected from one or more of deuterium, methyl, and deuterated methyl; L is selected from a direct bond, a substituted or unsubstituted phenyl group, a substituted or unsubstituted biphenyl group, and the L substituent is selected from one or more of deuterium, methyl, and deuterated methyl; R1 and R2 are independently selected from one or more of hydrogen, deuterium, tert-butyl, and deuterated tert-butyl; A1-A7 are hydrogen or deuterium, and at least one of A5-A7 is deuterium; The present invention does not include the following compounds: 。 2. A compound according to claim 1, characterized in that The compound is one of the following structural formulas: 。 3. A composition comprising the compound according to any one of claims 1-2.
4. An organic electroluminescent device comprising the material according to claim 1, characterized in that: The organic electroluminescent device comprises a first electrode, a second electrode and an organic layer formed between the first electrode and the second electrode, wherein the organic layer contains the organic electroluminescent compound as claimed in any one of claims 1 to 2 or the composition as claimed in claim 3.
5. The organic electroluminescent device according to claim 4, characterized in that: The organic layer comprises a hole injection layer, a hole transport layer, a second hole transport layer, a light-emitting layer, a hole blocking layer, an electron transport layer, and an electron injection layer; at least one of the hole injection layer, the hole transport layer, the second hole transport layer, the light-emitting layer, the hole blocking layer, the electron transport layer, and the electron injection layer contains the organic electroluminescent compound described in any one of claims 1 to 2.
6. The organic electroluminescent device according to claim 5, characterized in that: The second hole transport layer contains the organic electroluminescent compound according to any one of claims 1 to 2 or the composition according to claim 3.
7. The organic electroluminescent device according to claim 4, characterized in that: The compound of the invention is applied to the organic electroluminescent device, and the organic electroluminescent device is applied to the field of manufacturing electronic display equipment or OLED lighting equipment.
Citation Information
Patent Citations
Spirobifluorene compounds for organic electroluminescent devices
CN104114672A
Spirobifluorene organic electroluminescent compound and organic electroluminescent device
CN112010760A
Materials for electronic devices
CN116323559A
Spiro compound containing asymmetric alkyl substitution and organic electroluminescent device
CN118026856A